Motif Naga pada Hinggi Sumba Timur Sebuah Metamorfosa Estetik - Biranul Anas (Journal of Visual Art and Design, 2007)
Hinggi, a traditional ikat cloth, is one of East Sumba's foremost material culture. As a component of the East Sumbanese traditional man's dress, hinggi is visually impressive. Its patterns display attractive motives, decorative and symbolic, that depict religious conviction, power, wealth, status, honor and gender prestige, based on local and foreign sources that comply to traditional standards of quality. Intrinsically it indicates hinggi's central role in social and ritual context, making it a highly prized item among the East Sumbanese, a matter that has been taken place since ancient days, and the international audience as well. Throughout its long history, the making of the hinggi came in contact with outside powers i.e. through trade, colonialism, education, and industrialization, including today's international tourism. From a cloth that functioned to serve the internal culture of its producers, hinggi became a commodity for outsiders that consequently affected its aesthetical aspects. Hinggi's patterning went through changes towards new forms adjusting to external demand, especially for the past 30 years, resulting in salient differences between hinggis made for sale and those made for internal use. Significant visual changes are that of the introduction of secular designs depicting local cultural themes such as ceremonies and mock battles, conveyed in realistic expressions with  smooth lines in a coinciding asymmetric configuration within a narrative set up, replacing traditional spiritual iconography which is relatively stylistic, abstract and stiff, in a diametrical symmetric setting with no expository relation. New hinggi designs principally sprung up from three main themes i.e. the papanggang, a spectacular burial ceremony carried out for personalities of high social status; the pasola, a ceremonial (in the past real) battle between opposing parties; and the palai ngandi, a folk tale about the groom's kidnapping of his bride. The three themes are presented in numerous variations, partly in combination with traditional symbolic motives, which now play a minor role in the overall configuration, besides the many more without them. However, the new designs have no role in East Sumba's tradition. Traditionally designed hinggis continue to exist due to their importance in the East Sumbanese internal culture.